PENGARUH IKLIM ORGANISASI TERHADAP TINGKAT BURNOUT PADA TENAGA KEBERSIHAN (CLEANING SERVICE) DI LINGKUNGAN PT PELINDO DAYA SEJAHTERA DENGAN KOMUNIKASI INTERPERSONAL SEBAGAI MEDIATOR - Kusuma, Adrianto Prayoga; Herachwati, Nuri (ITB AAS Indonesia Surakarta, 2023)
Cleaning service at PT PDS is one of the professions that is prone to Burnout, a condition where syndromes appears in employees in the form if emotional exhausting, dehumanization, etc. that can harm individuals and organizations. Burnout conditions that are not handles properly by the Company will have an impact on losing employees due to the emergence of Intention to Leave. The turnover condition for PT PDS’ cleaning services in 2021 is quite worrying, as it reaches 7%. From several external factors that can affect an employee’s Burnout, organizational climate and interpersonal communication are the two most dominant factors in influencing an employee’s Burnout because both has direct contact with what is felt by the cleaning service at PT PDS. Quantitative research was then conducted on 301 PT PDS cleaning services who were randomly selected out of 1.218 cleaning services, and aimed to determine the direct and indirect effect of four variables: Organizational Climate, Interpersonal Communication, Burnout, and Intention to Leave. Data was collected using a questionnaire method, then analyzed using the t statistic and the comparison of t table values and significant p values to test the hypothesis. The result shows that four hypotheses are accepted, namely: Organizational Climate has a direct influence to Burnout level of Cleaning Service at PT PDS; Interpersonal Communication has a direct influence to Burnout level of Cleaning Service at PT PDS; Organizational Climate has indirect influence to Burnout level of Cleaning Service at PT PDS; and Burnout has direct effect to Intention to leave of Cleaning Service at PT PDS.